Alcoholics Have More Tryptophan Hydroxylase 2 mRNA and Protein in the Dorsal and Median Raphe Nuclei. (18th June 2014) - Bach, Helene; Arango, Victoria; Kassir, Suham A.; Tsaava, Tea; Dwork, Andrew J.; Mann, J. John; Underwood, Mark D.
<x xml:space="preserve">Abstract</x> Background Chronic alcohol use depletes brain serotonin (5‐hydroxytryptamine [5‐HT]), yet we previously found more tryptophan hydroxylase 2 (TPH2), the rate‐limiting biosynthetic enzyme for 5‐HT, in the dorsal raphe nucleus (DRN) of alcoholics. We sought to determine whether the increase in amount of TPH2 enzyme is associated with more TPH2 mRNA gene expression in the DRN of a new cohort of alcoholics and controls. Methods TPH2 mRNA and protein were measured by in situ hybridization and immunoautoradiography, respectively, in the DRN and median raphe nucleus (MRN) of age‐ and sex‐matched pairs (n = 16) of alcoholics and nonpsychiatric controls. Alcohol use disorder diagnosis and medical, psychiatric, and family histories were obtained by psychological autopsy. Age and sex were covariates in the analyses. Results TPH2 mRNA in alcoholics was greater in the DRN and MRN compared to controls (DRN: controls: 3.6 ± 1.6, alcoholics: 4.8 ± 1.8 nCi/mg of tissue, F = 4.106, p = 0.02; MRN: controls: 2.6 ± 1.2, alcoholics: 3.5 ± 1.1 nCi/mg of tissue, F = 3.96, p = 0.024). The difference in TPH2 mRNA was present in all DRN subnuclei (dorsal [DRd]: 135%, interfascicular [DRif]: 139%, ventral [DRv]: 135%, ventrolateral [DRvl]: 136% of control p < 0.05) except the caudal subnucleus. Alcoholics also had more TPH2 protein in the DRN and MRN than controls (DRN: controls: 265 ± 47, alcoholics: 318 ± 47 μCi/g, F = 8.72, p = 0.001; MRN: controls: 250 ± 33, alcoholics: 345 ± 39 μCi/g, F = 7.78, p = 0.001). There is a positive correlation between TPH2 protein and mRNA expression in the DRN (r = 0.815, p < 0.001), suggesting that the higher amount of TPH2 protein is due to an increase in TPH2 gene expression. Conclusions These findings suggest that greater TPH2 gene expression is the basis for more TPH2 protein in the DRN and MRN in alcoholics.